Pseudodominant Nanophthalmos in a Roma Family Caused by a Novel PRSS56 Variant - Lubica Dudakova; Pavlina Skalicka; Olga Ulmanová; Martin Hlozanek; Viktor Stranecky; Frantisek Malinka; Andrea L. Vincent; Petra Liskova (Journal of Ophthalmology)
Background. The aim of the study was to identify the molecular genetic cause of two different Mendelian traits with ocular involvement present in the members of a single consanguineous Czech Roma family. Methods. We have performed ocular examination and review of medical records in two individuals diagnosed with nanophthalmos (proband and her father) and one individual followed for bilateral congenital cataract and microcornea (uncle of the proband). DNA of subjects with nanophthalmos was analysed by exome sequencing. Sanger sequencing was applied for targeted screening of potentially pathogenic variants and to follow segregation of identified variants within the family. Results. A homozygous variant c.1509G>C; p.(Met503Ile), in PRSS56 was found in the two individuals affected with nanophthalmos. The change was absent from the gnomAD dataset, but two out of 118 control Roma individuals were also shown to be heterozygous carriers. Analysis of single nucleotide polymorphisms in linkage disequilibrium with the c.1509G>C in PRSS56 suggested a shared chromosomal segment. The nanophthalmos phenotype, characterized in detail in the younger individual, encompassed bilateral corneal steepening, retinal folds, buried optic head drusen, and restricted visual fields, but no signs of retinal dystrophy. A known pathogenic founder CTDP1 variant c.863+389C>T in a homozygous state was identified in the other family member confirming the suspected diagnosis of congenital cataracts, facial dysmorphism, and demyelinating neuropathy syndrome. Conclusions. Herein, we report the first occurrence of nanophthalmos in the Roma population. We have identified pseudodominant inheritance for this phenotype caused by a novel variant in PRSS56, representing a possible founder effect. Despite advances in genetic technologies such as exome sequencing, careful phenotype evaluation in patients from an isolated population, along with an awareness of population-specific founder effects, is necessary to ensure that accurate molecular diagnoses are made.